Macroscopic Supramolecular Assembly of Rigid Building Blocks Through a Flexible Spacing Coating. (22nd January 2014) - Cheng, Mengjiao; Shi, Feng; Li, Jianshu; Lin, Zaifu; Jiang, Chao; Xiao, Meng; Zhang, Liqun; Yang, Wantai; Nishi, Toshio
<x xml:space="preserve">Abstract</x> Macroscopic supramolecular assembly is a promising method for manufacturing macroscopic, ordered structures for tissue‐engineering scaffolds. A flexible spacing coating is shown to overcome undesired surface and size effects and to enable assembly of macroscopic cubes with host/guest groups. The assembled pairs disassembled upon introduction of competitive guest molecules, thereby demonstrating a multivalent assembly mechanism. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>